EVALUASI SISTEM DRAINASE TERHADAP PENANGGULANGAN BANJIR DI PERUMAHAN JATIBENING PERMAI KOTA BEKASI - Suprapti; Acep Hidayat; Muhammad Isradi; Hendy Yusman Firdaus; Muhammad Ikhsan Setiawan (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2022)
Residential area of Jatibening Housing located in Jln. Caman Raya No. 2,Jatibening Village, Pondok Gede Subdistrict, Bekasi City. The condition of drainage in the Jatibening Permai Housing is currently not as good as a whole. This is evidenced by the flooding that still occurs when the rainy season arrives. So that the evaluation and re-planning of the drainage channel must be done by analyzing the calculation of Cross Section data and rainfall data so that the drainage channel dimensions are obtained. This is so that Jatibening Permai Housing is no longer a flood-affected area due to high rainfall. The results of the study show that the reuse period used in channel planning drainage at Jatibening Permai Housing is a 2-year return period with the Type III Log Pearson Method. The planned flood discharge was analyzed by the rational method based on rainfall intensity from the maximum daily rainfall data in the 10 year period of 212.05 mm / hour. The maximum flood discharge of the Jatibening Permai residential area is 1,650 m ^ 3 / second. While planning an infiltration pond in the form of a rectangle measuring 75 m x 55 m with a depth of 5 m can accommodate a volume of rainwater of 20,625 m3.